Rich haplotypes of Viviparous‐1 in Triticum aestivum subsp. spelta with different abscisic acid sensitivities. (12th May 2016) - Feng, Yumei; Qu, Ruoduan; Liu, Simeng; Yang, Yan
Abstract: BACKGROUND: Viviparous‐1 ( Vp‐1 ) is a major gene affecting pre‐harvest sprouting (PHS) in common wheat, and improving PHS tolerance is a crucial factor for wheat breeding. Spelt wheat is always used as the donor parent to improve resistance and quality in wheat breeding: however, the roles of the Vp‐1 genes in spelt wheat and their relationship to common wheat remain uncertain. The current study aimed to isolate and characterise Vp‐1 haplotypes in spelt wheat ( Triticum aestivum subsp. spelta ). RESULTS: In spelt wheat, a total of eight new Vp‐1 haplotypes were identified: TaVp‐1Ap, TaVp‐1Aq and TaVp‐1Ar in the A genome; TaVp‐1Bj, TaVp‐1Bh and TaVp‐1Bi in the B genome; and TaVp‐1Da and TaVp‐1Db in the D genome. According to RT‐PCR results, correctly spliced transcripts were more highly expressed in some haplotypes than in others, and their expression was highly associated with their distinct responsiveness to abscisic acid (ABA) exposure. The mis‐splicing of Vp‐1 transcripts and several indel variations detected in spelt wheat appear to have been retained through the hybridisation process. CONCLUSION: Certain haplotypes detected in spelt wheat might be valuable in the breeding and selection of germplasm to improve PHS issues in wheat. © 2016 Society of Chemical Industry